Alternating Copolymer of Double Four Ring Silicate and Dimethyl Silicone Monomer–PSS‐1. Issue 47 (17th July 2017) - Smet, Sam; Vandenbrande, Steven; Verlooy, Pieter; Kerkhofs, Stef; Breynaert, Eric; Kirschhock, Christine E. A.; Martineau‐Corcos, Charlotte; Taulelle, Francis; Van Speybroeck, Veronique; Martens, Johan A.
Abstract: A new copolymer consisting of double four ring (D4R) silicate units linked by dimethylsilicone monomer referred to as polyoligosiloxysilicone number one (PSS‐1) was synthesized. The D4R building unit is provided by hexamethyleneimine cyclosilicate hydrate crystals, which were dehydrated and reacted with dichlorodimethylsilane. The local structure of D4R silicate units and dimethyl silicone monomers was revealed by multidimensional solid‐state NMR, FTIR and modeling. On average, D4R silicate units have 6.8 silicone linkages. Evidence for preferential unidirectional growth and chain ordering within the PSS‐1 copolymer was provided by STEM and TEM. The structure of PSS‐1 copolymer consists of twisted columns of D4R silicate units with or without cross‐linking. Both models are consistent with the spectroscopic, microscopic and physical properties. PSS‐1 chains are predicted to be mechanically strong compared to silicones such as PDMS, yet more flexible than rigid silica materials such as zeolites. Abstract : Linking up : Systematic linking of D4R double four ring silicate with dimethylsilicone monomers generates silicone copolymer with enhanced mechanical and thermal stability. The synthesis of the new PSS‐1 material (polyoligosiloxysilicone) proceeds by contacting anhydrous [C6 H14 N]4 [Si8 O16 (OH)4 ] crystals with dichlorodimethylsilane in organic solvent. The identification of PSS‐1 was done using multidimensional solid‐state NMR spectroscopy, FTIR, STEM, TEM, and modeling.